A prospective observational study on incidence of adverse drug reactions in a tertiary care teaching hospital: a pharmacovigilance study - Kalyani, S. Sre Akshaya; Srihitha, Pendota; Abhinay Sharma, Katnapally; Dharanija, Porandla; Bheemreddy, Sandeep Kumar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: An adverse drug reaction (ADRs) is determined as response to a drug that is noxious unintended excludes therapeutic failures, overdose, drug abuse, noncompliance, and medication errors. The main aim of the study is to detect, understand and report ADR’S. Methods: This study is prospective observational study conducted for 6 months in in-patient setting in a tertiary care hospital. Naranjo’s, WHO causality scale, Siegel scale, Schumock and Thornton scale are used to assess ADR. Graph Pad Prism and SAS software’s are used. Results: Data was collected from a total of 1000 patients of which 121 (12.1%) patients were effected with 150 ADRs. Among 121 patients AdrAd was 60.66% and AdrIn was 39.33%. Of 121 patients 97 patients with single ADR, 28 patients with 2 ADRs, 10 patients were with three ADRs. ADR onset divides acute (10%), Latent (39%) and sub-acute (51%). ADR occurred are recovered (54%), Recovering (13%). Naranjos scale interprets definite (0.9%), probable (50.9%), possible (42.97%). According to WHO scale certain (2.7%), unlikely (2.7%), possible (38.84%). Hartwig and Siegel scale results are mild (12.4%), moderate (66.12%) and severe (12.4%). Schumock and Thornton preventability results are definitely (25.45%), probably (68.18%) and not preventable (6.36%). Conclusions: Every health care professional should be aware of the Pharmacovigilance principles and also should be aware of suspected ADR reporting form of PVPI. By applying the above scales it is easy for health care professionals to assess an ADR.